ANALISIS USAHATANI DAN PEMASARAN ASAM GELUGUR DI KABUPATEN DELI SERDANG - Muhammad Buhari Sibuea; Muhammad Thamrin; Khairunnas , (AGRIUM: Jurnal Ilmu Pertanian, 2012)
The first aim of this study was to determine the influence of factors of production land , labor , seeds , fertilizers to farmers' income , secondly the feasibility of farming , knowing the third line trading system . Research by census sampling method takes all the existing population . Data were analyzed with the Cobb Douglass function , input output ratio and descriptive . The results showed that simultaneous production factors land , labor , seeds , fertilizer significantly affect earnings at 95% confidence level . Partially land and fertilizer significantly affect earnings , while labor and seedlings did not significantly affect earnings . Value of input output ratio of 4.43 means very viable farming gelugur acid . Marketing channels in the study area there are two channels , the first channel from farmers to traders and merchants to large / agents and to the processor ; channel both from farmers to wholesalers / agents later to processingKeyword : gelugur acid, farming, marketing